1962
DOI: 10.1103/physrev.125.975
|View full text |Cite
|
Sign up to set email alerts
|

Optical-Model Analysis of Elastic Scattering of Protons on Carbon at Intermediate Energies

Abstract: Differential cross sections and polarizations for the elastic scattering of protons by carbon at energies between 7 and 20 Mev have been analyzed according to the diffuse-surface optical model of the nucleus. The model parameters were varied systematically, the best fits to the experimental data being determined by a method of least squares. Various forms of the absorptive part of the potential were investigated, although the main part of the analysis was carried out with a surface-plus-volume absorption poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1963
1963
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In the previous results [7], the elastic scattering on intermediate-mass and heavy nuclei can be analyzed successfully without renormalization of the strength of the real folded potential. To evaluate the validity of this argument for the case of light nuclei 12,13 C, we remained unchanged N R = 1 and only adjusted slightly the strength of imaginary potentials, while the phenomenological spin-orbit potential was used [11]. From the optical model results obtained with the CDM3Y6 interaction shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the previous results [7], the elastic scattering on intermediate-mass and heavy nuclei can be analyzed successfully without renormalization of the strength of the real folded potential. To evaluate the validity of this argument for the case of light nuclei 12,13 C, we remained unchanged N R = 1 and only adjusted slightly the strength of imaginary potentials, while the phenomenological spin-orbit potential was used [11]. From the optical model results obtained with the CDM3Y6 interaction shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is pointed out that the limitation of the present microscopic approach. Within the phenomenological optical model approach, Nodvik et al [11] indicated that the absorbed (imaginary) surface potential at these energies is more dominant than the absorbed volume potential, while the imaginary folded potential based on JLM interaction is only defined as a central volume potential. The addition of imaginary surface potential is necessary due to the fact that it is characterized by the effect of strong coupling at low energies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations